(untitled) - Dobson, Melanie (Thorndike, Maine, 2024)
"1907. On the eve of her fifth birthday, Poppy Pendleton is tucked safely in her bed, listening to her parents entertain New Yorks gilded society in their Thousand Islands castle; the next morning, she is gone, and her father is found dead in his smoking room. 1992. Though Chloe Ridell lives in the shadows of Poppys castle, now in ruins, she has little interest in the mystery that still captivates tourists and locals alike. She is focused on preserving the island she inherited from her grandparents and reviving their vintage candy shop. Until the day a girl named Emma shows up on Chloes doorstep, with few possessions, save a tattered scrapbook that connects her to the Pendleton family. When a reporter arrives at Chloes store, asking questions about her grandfather, Chloe decides to help him dig into a past shed thought best left buried. The haunting truth about Poppy, they soon discover, could save Emmas life, so Chloe and Logan must work together to investigate exactly what happened long ago on Koster Isle."--
Keywords: Family secrets; Fiction; Islands; Fiction; Missing children; Fiction; Thousand Islands (N.Y. and Ont.); Fiction; New York (N.Y.); History; 1898-1951; Fiction; New York (N.Y.); History; 20th century; Fiction; Christian fiction; Large print books; Historical fiction